The muscle and neural architecture of Taenia crassiceps cysticerci revisited; implications on head-tail polarization of the larvae - Calderón-Gallegos, Arturo; Tapia-Rodríguez, Miguel; Estrada, Karel; Rios-Valencia, Diana G.; de la Torre, Patricia; Castellanos-de Oteyza, Nicolás; Morales, Miguel A.; Bobes, Raúl J.; Laclette, Juan P. (Frontiers in Cellular and Infection Microbiology, 2024)
Taenia crassiceps has been used for decades as an experimental model for the study of human and porcine cysticercosis. Even though, its life cycle, tissue organization, ultrastructure and immune response elicited in the host, have been extensively described, there are many other biological questions remaining to be addressed. In the present study we revisited the muscle and neural architecture of cysticerci in two of the most frequently used strains (WFU and ORF), using conventional staining and confocal microscopy imaging, aiming to assemble an updated anatomy. Differences between both strains, including polarization processes during development of the young budding larvae, are emphasized. We also performed a search for genes that have been related to peptidergic neural processes in other related flatworms. These findings can help to understand the anatomical and molecular consequences of the scolex presence or absence in both strains.